2005
DOI: 10.1007/s10164-005-0160-8
|View full text |Cite
|
Sign up to set email alerts
|

Vertical and horizontal distribution patterns of the giant sea anemone Heteractis crispa with symbiotic anemonefish on a fringing coral reef

Abstract: Vertical and horizontal distribution patterns of the giant sea anemone Heteractis crispa with symbiotic anemonefish on a fringing coral reef ARTICLE Abstract The distribution patterns of the leathery sea anemone, Heteractis crispa, which contains an algal endosymbiont (zooxanthellae) and anemonefish, were investigated in relation to size distribution on a shallow fringing reef (3.2 ha, 0-4 m depth) in Okinawa, Japan. Individual growth and movements were also examined. Large individuals (>1,000 cm 2 ) inhabited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
(48 reference statements)
1
15
0
Order By: Relevance
“…A similar phenomenon is observed in another giant sea anemone Heteractis crispa, which inhabits shallow reef edges in a fringing coral reef (Hattori 2006): individuals are more abundant in shallow reefs (<0.5 m deep), where few large individuals are found, and larger individuals are found in deeper habitats (<4 m deep) of the reef edges, where few small individuals are found. Hattori (2006) suggests that anemones in the deep habitats, which are suitable for their growth, suffer from high predation pressures when juveniles, while those in the shallow habitats, which provide with refuges consisting of corals, suffer from higher levels of physiological stress such as higher water temperature. For S. gigantea, in this study, individuals on the patch reefs inhabited slightly deeper than those on the shallow sandy bottoms nearby the dense seagrass beds.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…A similar phenomenon is observed in another giant sea anemone Heteractis crispa, which inhabits shallow reef edges in a fringing coral reef (Hattori 2006): individuals are more abundant in shallow reefs (<0.5 m deep), where few large individuals are found, and larger individuals are found in deeper habitats (<4 m deep) of the reef edges, where few small individuals are found. Hattori (2006) suggests that anemones in the deep habitats, which are suitable for their growth, suffer from high predation pressures when juveniles, while those in the shallow habitats, which provide with refuges consisting of corals, suffer from higher levels of physiological stress such as higher water temperature. For S. gigantea, in this study, individuals on the patch reefs inhabited slightly deeper than those on the shallow sandy bottoms nearby the dense seagrass beds.…”
Section: Discussionsupporting
confidence: 75%
“…There was no S. gigantea without anemonefish. The area covered by the tentacles of each actinia was regarded as an oval and was measured and calculated (long axial length · short axial length · p/4) (Hattori 2002(Hattori , 2005(Hattori , 2006. All S. gigantea were individually recognized by their locations on the map and body sizes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, host abundance may have depended upon the product of TA and TP. A host anemone species (Heteractis crispa) is known to be more abundant in the shallow edges of reefs than in the shallowest parts in a fringing reef of Sesoko Island, Okinawa, because physiological stress (extreme temperature, aerial exposure and wave action) is less severe and hard and soft corals are more abundant at the reef edges, which provide the host with refuge and shelters (Hattori 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In Heteractis crispa, Hattori (JE 2006) [12] found that the sizes of anemones were positively correlated with their water depth in Japan. However, in the present investigation, the size of the three most common host anemones showed a very weak correlation with the water depth.…”
Section: Discussionmentioning
confidence: 98%